Let's Choose Healthy Snacks! Increasing Knowledge of Elementary School Children with Edutainment - Hadriani, Hadriani; Wilyanti, Desrina; Pani, Widya; Gusman, Gusman; Batjo, Siti Hadijah; Udin, Udin (Buletin Penelitian Kesehatan, 2026)
Background: Children's habits in elementary school for snacks are often not supported by a proper understanding of healthy food choices, so they prefer to choose foods that contain a lot of sugar, salt, and fat. The lack of interesting and appropriate nutritional information for children makes their knowledge about healthy snacks still very minimal. To overcome this problem, the edutainment method that combines education and entertainment can be an effective solution. With fun ways like games or interactive stories, children can more easily understand the importance of choosing healthy snacks. Objective: This study aims to determine the influence of edutainment on the knowledge of elementary school children about the selection of healthy snacks in SD Muhammadiyah 1 Palu. Methods: This study used a Pre-Experiment type of research with One Group Pretest Posttest Design. This research was carried out on May 17-June 03, 2024 at SD Muhammadiyah 1 Palu in the working area of the Kamonji Health Center. The population of this study is all 3rd grade students totaling 20 people. The sampling method uses total sampling. The questionnaire contains 10 statements and the scale used is Guttman's. The edutainment method is in the form of an animated video that is inserted into the game. An animated video containing a collection of images or cartoons with a duration of 4 minutes 36 seconds is given once about the selection of healthy snacks including the definition of snacks, functions, sources, impacts, and criteria for choosing healthy snacks. The analysis of this study uses the Wilcoxon test. Results: The results of the univariate analysis pretest student knowledge were good at 5.0%, fair 15.0%, and less than 80.0%. After the edutainment method was carried out, the students' knowledge increased to either 60.0% and 40.0% adequate. Edutainment method intervention was given with the results of the posttest of good knowledge 60% and 40.0%. The Wilcoxon test was negative rank 0, positive rank 20 and ties 0 p-value was 0.001<0.05. Conclusion: The edutainment method has an effect on increasing knowledge about the selection of healthy snacks in students at SD Muhammadiyah 1 Palu. It is hoped that homeroom teachers can motivate students to further improve the habit of choosing healthy snacks with more interesting learning methods such as Edutainment, which is learning that is inserted with games to make the learning process more fun.